IMF Staff papers : Volume 18 No. 3. (IMF Staff Papers; IMF Staff Papers, 1971)
This paper discusses the implications for credit policy of changes in the income velocity of money; it neglects other policy elements of financial programs unless they have a direct bearing on velocity changes. Control over credit expansion by domestic banks is used to influence expenditure decisions, since the availability of credit has a strong impact on expenditures on domestic and foreign goods and services and, possibly, on net capital flows and, therefore, on the balance of payments. The paper also describes some relationships between monetary and national income accounts in order to identify the changes in velocity that must be considered in determining credit policies. The relevance of incorporating lags into the demand for money function has been mentioned earlier. Lags in the formation of expectations within a country usually can be expected to change only slowly over time and, therefore, can be assumed constant in the estimation of the demand for money function.